A Modified DOE-2 Model for Typical Performance of Absorption Chillers and its Application - 杨承; 杨泽亮; 蔡睿贤 (Zhileng xuebao)
LiBr-water absorption chillers are commonly adopted in multifunction energy systems. The empirical part-load performance model for chillers presented by DOE-2 is one of the analytical methods to solve chiller performances. In this study, the applicability of the DOE-2 model for absorption chillers was analyzed. A modified DOE-2 model for double effect steam-driven absorption chillers, as an example, was developed and its reasonability and validity were tested by the product data and the general theoretical model. Application case study confirms the ability of the modified DOE-2 model to fast predict the part-load performances of absorption chillers.